'Crazy love': nonlinearity and irrationality in mate choice. (January 2019) - Ryan, Michael J.; Page, Rachel A.; Hunter, Kimberly L.; Taylor, Ryan C.
Abstract : Choosing a mate is one of the most important decisions an animal can make. The fitness consequences of mate choice have been analysed extensively, and its mechanistic bases have provided insights into how animals make such decisions. Less attention has been given to higher-level cognitive processes. The assumption that animals choose mates predictably and rationally is an important assumption in both ultimate and proximate analyses of mate choice. It is becoming clear, however, that irrational decisions and unpredictable nonlinearities often characterize mate choice. Here we review studies in which cognitive analyses seem to play an important role in the following contexts: auditory grouping; Weber's law; competitive decoys; multimodal communication; and, perceptual rescue. The sum of these studies suggest that mate choice decisions are more complex than they might seem and suggest some caution in making assumptions about evolutionary processes and simplistic mechanisms of mate choice. Highlights: Mate choice decisions are sometimes irrational. Auditory grouping is not always an easy task for choosers. Comparisons can be based on proportional rather than absolute differences. Mate preferences can be influenced by competitive decoys. Novel combinations of audio and visual cues can result in perceptual rescue.